2013
DOI: 10.1089/scd.2012.0167
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet B Preconditioning Enhances the Hair Growth-Promoting Effects of Adipose-Derived Stem Cells Via Generation of Reactive Oxygen Species

Abstract: Hypoxia induces the survival and regenerative potential of adipose-derived stem cells (ASCs), but there are tremendous needs to find alternative methods for ASC preconditioning. Therefore, this work investigated: (1) the ability of low-dose ultraviolet B (UVB) radiation to stimulate the survival, migration, and tube-forming activity of ASCs in vitro; (2) the ability of UVB preconditioning to enhance the hair growth-promoting capacity of ASCs in vivo; and (3) the mechanism of action for ASC stimulation by UVB. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 41 publications
(47 reference statements)
0
48
0
1
Order By: Relevance
“…The regenerative potential of ASCs and the paracrine effect of ASCs differ according to the stimulators used [12,15,[45][46][47]. For example, hypoxia upregulated VEGF and bFGF, which enhanced wound healing and hair-regenerative potential of ASCs [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The regenerative potential of ASCs and the paracrine effect of ASCs differ according to the stimulators used [12,15,[45][46][47]. For example, hypoxia upregulated VEGF and bFGF, which enhanced wound healing and hair-regenerative potential of ASCs [12].…”
Section: Discussionmentioning
confidence: 99%
“…An area on the back of 7-week-old C 3 H/HeN mice in the telogen stage of the hair cycle was shaved with clippers and electric shaver, and special care was taken to avoid damaging the bare skin [15,26]. Before injection into the mice, ASCs were treated with vitamin C (200 mM).…”
Section: Animal Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…31 The keratinocytederived vascular endothelial growth factor (VEGF, also known as VPF or vascular permeability factor) provides the major cutaneous angiogenic activity in epidermal keratinocytes and its overexpression results in hyperpermeable dermal capillaries. 32 34 In a previous study, hypoxia through generation of ROS was shown to increase the survival of human ASCs, and the conditioned medium derived from hypoxiapreconditioned ASCs supported endothelial cell survival and endothelial tube formation. 35 Hypoxia preconditioning also enhanced the wound-healing capacities of ASCs.…”
Section: Discussion Of Findings and Relevant Literaturementioning
confidence: 92%
“…36 Low-dose UVB pretreatment of ASCs in vitro, just as in hypoxia preconditioning, induced ASC survival, migration, angiogenesis, and growth factor stimulation and this was attributed to Nox4-induced ROS generation. 34 Upon absorption of UVB photons, 7-dehydrocholesterol located within keratinocytes is converted to previtamin D3, which is then isomerized to vitamin D3 and later on converted to active form of vitamin D-1,25(OH) 2 D. 1,25(OH) 2 D in the skin activates innate immune responses, such as the production of antimicrobial peptides, which can enhance microbial killing and the stimulation of macrophage differentiation and phagocytosis. 37 …”
Section: Discussion Of Findings and Relevant Literaturementioning
confidence: 99%